Neutron-diffraction study of the cubic-tetragonal phase structural transition in the single crystals of the solid solutions of zirconium and yttrium oxides - V. A. Sarin; A. A. Bush (Тонкие химические технологии)
Objectives. The determination of the phase relations, crystallographic characteristics, microstructure features, and atomic crystal structure of zirconium oxide crystals that are partially and completely stabilized by yttrium oxide additives, and the identification of the crystallographic and crystal-chemical correlations with the physicochemical properties of single crystals.Methods. The neutron structure of the crystals was studied using the neutron time-of-flight and constant wavelength methods using a high-resolution Fourier diffractometer on the IBR-2 pulsed fast reactor and a four-circle neutron diffractometer “Syntex.” Single crystals were grown by directed crystallization from the melts of mixtures (1 − х)ZrO2 ∙хY2O3 , х = 0.03 and х = 0.12 with different growth rates (10 and 40 mm/h).Results. It was observed that when growing single crystals with x = 0.03–0.05, the crystal was stratified into cubic and tetragonal phases, and the ratio between the phases depended on the growth rate. At a growth rate of 40 mm/h, the content of the cubic phase was insignificant. In the crystals of partially stabilized zirconium dioxide (ZrO2) with the additions of 3 mol % Y2O3, the coherent coexistence of cubic and tetragonal phases was established, and the twin law for a tetragonal component (rotation of unit cell axis by 90° around the a (b) axis) that was observed during the phase transition from high-temperature cubic phase to tetragonal phase was determined. For the fully stabilized zirconium oxide of the cubic symmetry (with 12 mol % Y2O3), the 0.3 Å displacements of oxygen atoms from their partial structural positions in the directions [100] and [111] were determined. These displacements correlated with the directions of the ion transport.Conclusions. Previous studies have shown that the ratio between the cubic and tetragonal phases of the single crystals of the ZrO2 –Y2O3 system depends on the growth rate of the single crystals. The content of Y2O3 in the cubic and tetragonal phases of a single crystal was determined using the non-destructive neutronography method on the same volume sample of a solid solution of this system. Moreover, the displacements of oxygen atoms from the main position of the crystal were determined.